Prevalence of a 23bp Insertion in Exon 3 of the Endothelial Cell Protein C Receptor Gene in Venous Thrombophilia - Depka, Mario von; Czwalinna, Andreas; Eisert, Roswith; Wermes, Cornelia; Scharrer, Inge; Ganser, Arnold; Ehrenforth, Silke (Thrombosis and Haemostasis, 2001)
Background: The endothelial cell protein C receptor (EPCR) enhances protein C activation by the thrombin-thrombomodulin complex. As evidence is accumulating that EPCR is an important component of the protein C anticoagulant pathway, polymorphisms in the EPCR gene might be candidate risk factors predisposing to venous thromboembolism (VTE). Recently, a 23bp insertion in exon 3 of the EPCR gene has been identified, which duplicates the preceding 23 bases and results in a STOP codon downstream from the insertion point. However, the clinical significance of this mutation in VTE remains to be clarified. Methods and Results: In this study we evaluated the EPCR 23bp insertion in 889 patients with documented VTE and in 500 healthy controls. The prevalence of the EPCR insertion among patients was 0.1%, which was not significantly different compared to controls (0.6%, p = 0.1). Conclusions: Our findings showed that the EPCR 23bp insertion is very rare in both patients with VTE and the general population and failed to support an association between the EPCR 23bp insertion and an increased risk of VTE.
Keywords: EPCR; venous thromboembolism; protein C pathway; genetics